Laminate film, sensor, and tape
The laminated film, with its specific multilayer structure and thermoplastic resin composition, addresses the challenges of achieving high shape fixing and restoring capabilities, offering enhanced rigidity, elasticity, and thermal responsiveness.
Patent Information
- Application Number
- JP2023149796
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-15
- Publication Date
- 2025-03-28
AI Technical Summary
Conventional smart polymer materials struggle to achieve a high balance between shape fixing and shape restoring capabilities, particularly in terms of rigidity and elasticity, due to the limitations of their molecular structure network and responsiveness to thermal stimulation during repeated use.
A laminated film with a structure of nine or more layers alternately laminated with thermoplastic resin A and B, where the loss tangents at different temperatures exhibit specific peak relationships, allowing for independent mechanical responses of each polymer layer and maintaining responsiveness while providing rigidity and flexibility.
The laminated film exhibits enhanced shape fixing and shape restoring capabilities, maintaining high tension in the in-plane direction and retaining responsiveness even after multiple cycles of deformation and restoration due to thermal stimulation.
Smart Images

Figure 2025042707000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention provides a laminated film, sensor, and tape that have a multi-layer laminate structure that enhances shape fixation / restoration responsiveness to thermal stimuli, and that combines flexibility and strength to enable repeated deformation / restoration over a long period of time. [Background technology]
[0002] Smart polymers that can change the shape of materials by changing their molecular structure micro- / macro-in response to external stimuli (heat, light, electricity, pH, magnetic field, etc.) have been actively researched and developed. Smart polymers are known to be made of resins that are mainly composed of polymer components that exhibit elastic shrinkage behavior and polymer components with high rigidity, and are made by kneading, dispersing, or distributing the two. After being molded into a desired shape such as a sheet, tube, or string, they are being put to practical use in various applications by utilizing their ability to deform when stimulated and to restore their shape when stimulated again after deformation. For example, in medical and sanitary materials, they are used for medical catheters by utilizing the change in elastic modulus of the polymer due to stimuli, and for casts and dressing material base materials by utilizing their shape fixity. In industrial applications, they are used for process heat shrinkable films and fastening parts by utilizing the shape restoring force due to heat shrinkage, and for temperature sensors by utilizing the volume expansion and temperature dependency of the refractive index. In particular, smart polymer materials that use thermal stimuli have attracted attention as being the simplest and most practical of stimuli (Patent Documents 1 and 2).
[0003] In addition, most of the usual thermoresponsive smart polymer materials are fixed in shape and do not deform at room temperature; they deform under high temperature conditions above a certain level, solidify when cooled, and return to their original shape when a thermal stimulus is applied to release the elastic contraction behavior. However, in recent years, the development of sheet materials that deform at human skin temperature, always exhibit drapeability when in contact with the skin, and can freely deform to fit the shape of the body has been reported (Patent Documents 3 and 4). In recent years, the demand for wearable devices has increased due to the growing interest in health care, and materials that can soften and deform near body temperature are being used as wearless materials and tape base materials for various medical and sanitary materials in the hope of eliminating the drawback of wearable devices, which is the feeling of wearing them.
[0004] Such stimuli-responsive smart materials, which can respond and deform only under the necessary conditions, are expected to be put to practical use in a wide range of industrial and consumer applications in the future. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] Japanese Patent Application Publication No. 4-122712 [Patent Document 2] Japanese Patent Application Publication No. 9-309986 [Patent Document 3] Patent Publication No. 2021-023499 [Patent Document 4] JP 2017-133011 A Summary of the Invention [Problem to be solved by the invention]
[0006] In smart polymer materials using conventional polymers that have been mixed by kneading and dispersion / distribution, two different polymer components are dispersed and coexist inside to form an island structure. However, in order to increase the rigidity, it is necessary to increase the amount of polymer with high rigidity to form the sea, and on the other hand, in order to increase the elastic stretchability, it is necessary to increase the amount of polymer with high elastic contraction to form the sea. It is difficult to achieve both high rigidity and elastic stretchability, and it is difficult to show high shape fixing ability and shape recovery ability. In addition, in smart polymer materials using conventional polymers that have been mixed by kneading and dispersion / distribution, the repeated deformation and restoration destroys the molecular structure network and changes the higher-order structure, which reduces the responsiveness of the polymer to thermal stimuli during continuous use, and both the amount of shape fixing and the amount of shape recovery decrease. In particular, in the case of film shape, it is often used by stretching in the in-plane direction, but there is also the issue that the material cannot restore its original shape during the process of changing to a structure suitable for response in the in-plane direction, and tensile strain remains.
[0007] Therefore, an object of the present invention is to provide a laminated film which can exhibit a high degree of shape fixation and shape recovery, has particularly high rigidity when pulled in the in-plane direction, and has good responsiveness to repeated tension. [Means for solving the problem]
[0008] That is, a preferred embodiment of the present invention is as follows. (1) A laminated film having a structure in which nine or more layers of A layer made of a polymer mainly composed of thermoplastic resin A and B layer made of a polymer mainly composed of thermoplastic resin B different from the thermoplastic resin A are alternately laminated, in which, when dynamic viscoelasticity measurement is performed at a frequency of 10 Hz over a temperature range from -80°C to Tm described below, there are two or more loss tangent (tan δ) peaks, and the relationship between the tan δ peak tan δ1 occurring at the lowest temperature (temperature T1 (°C)) and the tan δ peak tan δ2 occurring at the highest temperature (temperature T2 (°C)) is tan δ2 / tan δ1 ≧ 1.0. In addition, in accordance with JIS-K-7122 (1987), the highest melting point of the laminated film obtained by differential scanning calorimetry measurement under the conditions of a sample of 5 mg and a heating rate of 20 °C / min is defined as Tm, and the highest temperature among the glass transition temperature or melting point that appears in the region lower than Tm is defined as Tn. The layer showing a melting point within ±5 °C of the highest melting point Tm shown by the laminated film is defined as layer A, and the layer in which the higher temperature among the glass transition temperature or melting point of the layer shows ±5 °C of Tn shown by the laminated film is defined as layer B. (2) The laminated film according to (1), wherein when the loss tangent of layer A at temperature T (°C) is tanδA(T) and the loss tangent of layer B is tanδB(T), tanδA(T1) > tanδB(T1) and tanδA(T2) < tanδB(T2). (3) The laminated film according to (1) or (2), wherein the permanent strain is 15% or less when a strain of 50% is applied at Tn + 20 °C. (4) The laminated film according to any one of (1) to (3), wherein the thermoplastic resin A is crystalline. (5) The laminated film according to any one of (1) to (4), wherein the thermoplastic resin B is amorphous and the glass transition temperature of layer B is the above-mentioned Tn. (6) The laminated film according to any one of (1) to (5), wherein in the strain-stress curve in the tensile test at Tn + 20 °C, the inflection point first appears when the differential analysis is performed at a strain of 50% or more. (7) The laminated film according to any one of (1) to (6), wherein when the storage modulus of layer A at temperature T (°C) is GA(T) (GPa) and the storage modulus of layer B is GB(T) (GPa), 1.2GA(Tn - 10) < GB(Tn - 10) and GA(Tn + 10) ≥ 1.2GB(Tn + 10) are satisfied. (8) The laminated film according to any one of (1) to (7), wherein the lamination ratio is 0.3 or more and 1.5 or less. (9) The laminated film according to any one of (1) to (8), wherein the main component of the thermoplastic resin A is any one of polystyrene, polyester, polyurethane, and polyamide. (10) A sensor in which a stretchable conductive layer is laminated on the laminated film according to any one of (1) to (9). (11) The sensor according to (10), which is used by changing its shape or function within a temperature range of 20 to 100°C. (12) A tape comprising an acrylic or silicone adhesive layer provided on at least one surface of the laminate film according to any one of (1) to (9). (13) The tape according to (12), which is used by changing its shape or function within a temperature range of 20 to 50°C. Effect of the Invention
[0009] Even when deformation / restoration is performed multiple times in response to thermal stimuli, each polymer layer independently shows a mechanical response in the direction along the laminate interface, so there is little change in the molecular structure network state of the entire polymer material before and after deformation, making it possible to use it as a flexible film substrate that can be used while deforming / restoring over a long period of time. Furthermore, because the ratio of different polymers can be freely adjusted while maintaining the layer structure, it is possible to obtain a laminated film with an optimal laminate structure that shows responsiveness in the layer direction, maintains rigidity, and also has flexibility (stretchability / elasticity). [Brief description of the drawings]
[0010] [Figure 1] FIG. 2 is a schematic diagram showing an example of the relationship between the depth in the thickness direction and the contrast difference (gray level) in a cross-sectional observation image of a laminate film having an (AB)x alternating laminate arrangement. [Diagram 2] FIG. 2 is a schematic diagram showing an example of a loss tangent spectrum in dynamic viscoelasticity measurement of a laminated film. [Diagram 3] FIG. 1 is a schematic diagram showing a differential calorimetric spectrum of an example of a laminate film using a crystalline thermoplastic elastomer and an amorphous thermoplastic resin having a glass transition temperature at a temperature Tn. [Figure 4] FIG. 2 is a schematic diagram showing a differential calorimetric spectrum of an example of a laminate film using a crystalline thermoplastic elastomer and a crystalline thermoplastic resin that exhibits a glass transition temperature at a temperature Tn. [Diagram 5] FIG. 2 is a schematic diagram showing a method for calculating permanent set from a 50% stretch forming-reheating cycle test. [Figure 6] FIG. 2 is a schematic diagram of an example of a strain-stress curve when stretched at a temperature below Tn. [Figure 7] FIG. 2 is a schematic diagram of an example of a strain-stress curve when stretched at a temperature of Tn+20° C. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] The laminated film of the present invention will be described in detail below. A preferred embodiment of the laminated film of the present invention is a laminated film having a structure in which nine or more layers of A layer made of a polymer mainly composed of thermoplastic resin A and B layer made of a polymer mainly composed of thermoplastic resin B different from the thermoplastic resin A are alternately laminated, and when dynamic viscoelasticity measurement is performed at a frequency of 10 Hz in a temperature range from -80°C to Tm described later, the laminated film has two or more loss tangent (tanδ) peaks, and the relationship between the tanδ peak tanδ1 occurring at the lowest temperature (temperature T1 (°C)) and the tanδ peak tanδ2 occurring at the highest temperature (temperature T2 (°C)) is tanδ2 / tanδ1≧1.0.
[0012] In order to obtain a higher mechanical response to external thermal stimuli than that obtained by conventional single-layer film techniques using kneaded and dispersed polymers, the laminate film of the present invention is preferably a laminate film having a structure in which nine or more layers of A layer made of a polymer mainly composed of thermoplastic resin A and B layer made of a polymer mainly composed of thermoplastic resin B different from the thermoplastic resin A are alternately laminated.
[0013] Thermoplastic resins that are "different" refer to cases where any of the following applies: (1) the compositions are different; (2) the glass transition temperatures or melting points are different in differential scanning calorimetry (DSC); (3) the contrast of images after dyeing when cross-sectionally observed by transmission electron microscopy (TEM) is different; (4) the dielectric constants of each layer are different in EELS measurements described below; or (5) the elastic moduli are different.
[0014] "Different compositions" means that the following conditions for "same composition" are not met. "Same composition" means that the repeating units in the chemical structures of both thermoplastic resins are 95 mol% or more in common, or that 95 mass% of the components of the thermoplastic resins are in common when comparing their constituent components.
[0015] For example, in the case of the former, polyethylene terephthalate has as its main constituent unit a constituent unit (ethylene terephthalate unit) in which an ethylene glycol unit and a terephthalic acid unit are bonded by an ester bond, but when the amount of copolymerization component exceeds 5 mol%, such as polyethylene terephthalate obtained by copolymerizing homopolyethylene terephthalate and isophthalic acid at 10 mol%, the two thermoplastic resins are considered to have different compositions when they have a common chemical structure of polyethylene terephthalate. In addition, in the case of the latter, when one is homopolyethylene terephthalate and the other is a resin containing 90 mass% homopolyethylene terephthalate and the remaining 10 mass% is another component, the two thermoplastic resins are also considered to have different compositions when they have the same main constituent but have 5 mass% different components. The repeating unit structure of the specific composition / chemical structure of each thermoplastic resin can be identified by determining the layer thickness of each thermoplastic resin layer according to the methods described below in the "Laminated Cross-Section Image Acquisition" and "Layer Thickness Analysis" measurement methods, and then cutting and extracting the thermoplastic resin layer, or by scraping the layer to expose it as the outermost layer, using infrared spectroscopy (FT-IR method or nano-IR method), a gas chromatograph / time-of-flight mass spectrometer (GC-MS), or a nuclear magnetic resonance device (NMR).
[0016] On the other hand, if it is difficult to identify the composition by the above method while extracting each thermoplastic resin layer, the thermoplastic resin layers constituting the laminated film are judged to be "different" by showing different melting points and / or glass transition temperatures in differential scanning calorimetry (DSC). In the present invention, showing different melting points and different glass transition temperatures means that the melting points and glass transition temperatures differ by 2.0°C or more in the differential calorimetry spectrum when each thermoplastic resin layer is heated to a temperature above its melting point, then quenched and heated again. In addition, if the thermoplastic resin does not show a glass transition temperature or melting point in the measurement temperature range of -80°C to 280°C described in the section on differential scanning calorimetry (DSC) in the measurement method described later, if the thermoplastic resin constituting one layer shows a glass transition temperature or melting point and the thermoplastic resin constituting the other layer does not show a glass transition temperature or melting point, it cannot be calculated as a temperature difference, but the thermal properties of both resins may be interpreted as being different.
[0017] In addition, if it is difficult to identify by the above two methods, the layer interface due to the contrast difference can be confirmed in the cross-sectional image observed by transmission electron microscope observation, the brightness of each layer can be quantified, and if it can be confirmed that the difference in the average brightness of the two adjacent layers is greater than any of the standard deviations of the brightness of the adjacent thermoplastic resin layers, the adjacent thermoplastic resin layers are judged to be "different". If the composition of the thermoplastic resin constituting both thermoplastic resin layers is the same, it is considered that the thermoplastic resin layer formed using it will also show the same characteristics, so the sameness or difference of the thermoplastic resin can be judged from the state of the thermoplastic resin layer. Since this contrast occurs due to scattering of electron beams, crystal diffraction, etc., when the composition of the thermoplastic resin constituting the thermoplastic resin layer differs according to the above-mentioned criteria, the crystallinity and electron density state differ depending on the type and copolymerization amount of each thermoplastic resin, and the dyeing state differs, making it possible to visually recognize each layer as a layer structure with a contrast difference in the cross-sectional image of the laminate film.
[0018] In the case of a laminated film having two different types of thermoplastic resin layers, each thermoplastic resin layer shows a constant brightness, so if the depth in the thickness direction is plotted on the horizontal axis and the brightness and contrast (gray level in a grayscale display) at each point on the vertical axis, the graph will show repeated ups and downs between the brightness of two points, as shown in Figure 1. The symbols 1 to 3 in Figure 1 respectively represent the spectrum showing the relationship between the depth in the thickness direction and the change in contrast (gray level) of a laminated film having an (AB)n (n is a natural number) regular arrangement, the layer thickness of layer A, and the layer thickness of layer B, respectively.
[0019] If it is difficult to distinguish them by the contrast difference, the two thermoplastic resins are judged to be "different" from the dielectric constant of each thermoplastic resin layer obtained by electron energy loss spectroscopy (EELS measurement). As described above, the crystallinity and electron density state differ depending on the type and copolymerization amount of the thermoplastic resin, and the response (interaction) state of the molecules to the electromagnetic field changes, so that differences also appear in the electron scattering state, and a numerical difference in the dielectric constant depending on the material state appears. Specifically, an electron beam is irradiated to each thermoplastic resin layer in the cross-sectional sample, and the dielectric constant is analyzed to read the dielectric constant at a loss energy of 2.5 eV. If the difference in the dielectric constant of the obtained thermoplastic resin layers is 0.01 or more, the refractive index of the thermoplastic resin layers is judged to be "different".
[0020] Furthermore, if the thermoplastic resin layers cannot be determined to be "different" by the above four methods, according to the "AFM tapping measurement" described in the measurement method section below, when the cross-section of the laminated film is tapped while sweeping at a constant temperature, the two thermoplastic resin layers are determined to be "different" if the elastic modulus at the corresponding positions of the different thermoplastic resin layers shows a numerical difference of 1% or more. In particular, since the laminated film of the present invention is characterized in that the elastic modulus of both thermoplastic resins changes depending on the glass transition temperature, the elastic modulus may be measured at multiple temperatures (three or more points) that are 30°C or more different, and if a difference in elastic modulus is detected at any one point, the two thermoplastic resins may be determined to be "different".
[0021] Representative thermoplastic resins that can be used to form layers A and B of the laminated film of the present invention are shown below, but the thermoplastic resins that can be used in the present invention are not limited to those shown below. For example, polyolefin resins such as polyethylene, polypropylene, poly(1-butene), poly(4-methylpentene), polyisobutylene, polyisoprene, polybutadiene, polyvinylcyclohexane, polystyrene, poly(α-methylstyrene), poly(p-methylstyrene), polynorbornene, and polycyclopentene; polyamide resins such as nylon 6, nylon 11, nylon 12, and nylon 66; copolymer resins of vinyl monomers such as ethylene / propylene copolymer, ethylene / vinylcyclohexane copolymer, ethylene / vinylcyclohexene copolymer, ethylene / alkyl acrylate copolymer, ethylene / acrylic methacrylate copolymer, ethylene / norbornene copolymer, ethylene / vinyl acetate copolymer, propylene / butadiene copolymer, isobutylene / isoprene copolymer, and vinyl chloride / vinyl acetate copolymer; polyacrylate, polyisobutyl methacrylate, and polymethacrylate; Examples of the polymer that can be used include acrylic resins such as polymethyl methacrylate, polybutyl acrylate, polyacrylamide, and polyacrylonitrile; polyester resins such as polyethylene terephthalate, polypropylene terephthalate, polybutylene terephthalate, and polyethylene-2,6-naphthalate; biodegradable polymers such as polylactic acid and polybutyl succinate; and polyurethane, polyvinyl chloride, polyvinylidene chloride, polycaprolactone, polyvinyl acetate, polyvinyl alcohol, polyvinyl butyral, polyacetal, polyglycolic acid, polycarbonate, polyketone, polyether sulfone, polyether ether ketone, modified polyphenylene ether, polystyrene, polyphenylene sulfide, polyetherimide, polyimide, polysiloxane, tetrafluoroethylene resin, trifluoroethylene resin, trichloroethylene resin, tetrafluoroethylene-hexafluoropropylene copolymer, and polyvinylidene fluoride.
[0022] The laminated film consisting of different thermoplastic resin layers will be described in detail below, but thermoplastic resins with completely different structures can also be combined, and different thermoplastic resins can be made by alloying, blending, or copolymerizing.
[0023] It is desirable for the laminated film of the present invention to exhibit a function of being able to convert and restore the shape of the laminated film in a temperature range equal to or higher than a specific temperature. In order to achieve this function, it is preferable that at least one of the thermoplastic resins constituting the laminated film is a crystalline thermoplastic elastomer (TPE) resin that softens and exhibits elastic stretch behavior (rubber elastic behavior) in that temperature range. Elastic stretch behavior (rubber elastic behavior) cannot be achieved only by a composition that contains an aromatic ring and forms a strong structure by π conjugation and intermolecular forces, and is often achieved by including a soft segment component consisting of a relatively long aliphatic chain structure having 4 or more carbon atoms in the molecular structure by copolymerization or the like. In addition, in order for such elastic stretch behavior to be put to practical use in consumer and industrial applications, it is preferable that the thermoplastic elastomer exhibits elastic stretch behavior in the practical and processing temperature range of room temperature or higher and lower than 140°C, has a melting point in a temperature range higher than that, and exhibits heat resistance, flexibility, and high strength.
[0024] Examples of thermoplastic resins that can satisfy such characteristics include polyester-based TPEs (polyester resins containing polytetramethylene glycol copolymers, etc.), polyamide-based TPEs (polyether block amides, polyester amides, polyether ester amides, polycarbonate ester amides, etc.), thermoplastic polyurethane resins (aliphatic polyester urethane resins, aliphatic polyether urethane resins, etc.), polystyrene-based elastomers (styrene butadiene styrene resins, styrene isoprene styrene resins, styrene ethylene butylene styrene resins, ethylene ethylene propylene styrene resins, etc.), and polyolefin-based elastomers. In addition, resins obtained by dispersing / mixing these resins in an alloy can also be used. In addition, resins that do not exhibit elastic stretching behavior as the main components constituting the thermoplastic resin layer may be designed to become polymers that exhibit elastic stretching behavior by kneading and dispersing these components as additives.
[0025] Furthermore, in order for the laminated film of the present invention to exhibit the shape change / restoration function, it is desirable that the second thermoplastic resin different from the thermoplastic elastomer resin softens to such an extent that it does not exhibit rigidity when the above-mentioned specific temperature is exceeded. Specifically, as described later, it is preferable that the design is such that the magnitude of the elastic modulus of thermoplastic resin A and thermoplastic resin B is reversed at a specific temperature as a boundary. In addition, when the second thermoplastic resin softens, the thermoplastic resin may be in a rubber elastic state at the above temperature or higher, or may be melted and in a molten state, as long as it does not inhibit the expansion and contraction behavior of the TPE resin. The glass transition temperature or melting point of the second thermoplastic resin determines the shape transformation temperature of the laminated film as the above-mentioned specific temperature. In other words, in the temperature range in which the thermoplastic elastomer exhibits a rubber-like elasticity region, the second thermoplastic resin switches between solidification and softening, thereby realizing shape transformation and restoration. Therefore, since the thermal properties of the second thermoplastic resin are responsible for the shape transformation / restoration function, a thermoplastic resin may be appropriately selected according to the desired use and temperature range. Such a thermoplastic resin can be appropriately selected from the various thermoplastic resins listed above.
[0026] In addition, it is preferable that the thermoplastic elastomer resin exhibits crystallinity. The crystallinity mentioned here can be determined using a differential scanning calorimetry (DSC) analyzer. Specifically, in the spectrum obtained by extracting a layer containing the thermoplastic resin, heating it once to melt it, then quenching it, and heating it again, the crystalline thermoplastic resin is characterized by exhibiting three points: glass transition temperature, crystallization enthalpy which is an endothermic peak, and fusion enthalpy which is an exothermic peak. In particular, the fusion enthalpy is a characteristic that is not exhibited by amorphous resins. On the other hand, amorphous resins are characterized by not having fusion enthalpy and only exhibiting glass transition temperature. By making the elastomer resin crystalline, the processability, heat resistance, durability, chemical resistance, strength, etc. can be improved compared to amorphous resins, so this is preferable when considering the use of the laminated film of the present invention, which is used repeatedly. In addition, when extracting each layer, it is preferable to extract a layer at a location where there is no layer disorder and a layer structure is exhibited.
[0027] On the other hand, in order for the layers of two different types of thermoplastic resins constituting the laminated film to uniformly follow changes in shape and dynamically respond to the force that deforms the laminated film as a whole, it is preferable that the adjacent thermoplastic resins constituting each layer exhibit high compatibility to the extent that they exhibit non-peeling properties. Specifically, the compatibility between thermoplastic resins can be expressed as the difference in compatibility parameter (SP value). The compatibility parameter is a parameter related to the energy specific to the thermoplastic resin, and the closer these values are to each other, the higher the affinity is, such as the similarity of the skeletal structure, and the higher the adhesion at the resin layer interface is. The compatibility parameter can be estimated by calculation methods such as Hansen, Hoy, and Fedors, but the compatibility parameter of thermoplastic resins, which are organic polymer materials, will be calculated using the Fedors calculation method, which can be calculated based on the molecular structure of the resin. By using this method, the compatibility parameter of a thermoplastic resin containing a structural unit derived from a copolymerization component can also be easily calculated in ratio according to the ratio of each structural unit. In the Fedors calculation method, the cohesive energy density and molar volume of a molecule, which depend on the type and number of substituents, determine the compatibility parameter, and the compatibility parameter is estimated according to formula (1). Here, E coh (cal / mol) is the cohesive energy and V is the molar volume (cm 3 / mol).
[0028]
number
[0029] The compatibility parameter of the laminated film of the present invention is a value obtained by rounding off the estimated value calculated based on Fedor's formula to one decimal place. This method is described in F. Fedors, Polym. Eng. Sci., 14(2), 147 (1974).
[0030] In order for adjacent thermoplastic resin layers to exhibit good non-peeling properties, it is preferable that the difference in compatibility parameters (SP values) between adjacent thermoplastic resin layers is 2.5 or less. More preferably, the difference in SP value is 2.0 or less, and even more preferably 1.5 or less. In order to reduce the difference in SP value, the molecular skeleton of the repeating unit constituting the thermoplastic resin should be similar between adjacent thermoplastic resins in terms of aliphatic / aromatic, the chain length of the aliphatic difference, the type of functional group component, etc.
[0031] The layers A and B in the laminated film of the present invention are composed of polymers mainly composed of thermoplastic resin A and thermoplastic resin B, respectively. The main component as described here means a component contained in the polymer constituting the layer at more than 50% by mass and not more than 100% by mass. In this case, the thermoplastic resin may be a copolymer resin, an alloyed blend resin, or a thermoplastic resin obtained by kneading, dispersing, mixing and distributing two types of the same type of polymers that are the same resin components but have different compositions and properties such as polymerization degree and melt viscosity. Examples of minor components that are not the main components include minor components contained in the above-mentioned thermoplastic resins, such as inorganic components and low-molecular organic components with functionality other than thermoplastic resins, and specific examples thereof include light absorbers (ultraviolet absorbers, dyes, pigments, heat absorbers), antioxidants, light stabilizers, quenchers, heat stabilizers, weather stabilizers, organic lubricants, fillers, antistatic agents, nucleating agents, flame retardants, and antiblocking agents (various natural inorganic particles, inorganic synthetic particles, and organic components such as wax, fatty acid amides, and silicones). These sub-components can be freely added to each layer as long as the film's original shape fixing / deformation functions and physical properties are not impaired.
[0032] Among these subcomponents, depending on the type of thermoplastic resin constituting each thermoplastic resin layer, there are cases where deterioration is accelerated by absorbing ultraviolet light with high energy intensity. Therefore, it is also preferable to include an ultraviolet absorber or an antioxidant for the purpose of suppressing photodegradation by causing a competitive reaction.
[0033] When an alloyed blend resin is used as the resin constituting layer A or layer B, the thermoplastic resin constituting each layer refers to the thermoplastic resin that is the main component of the blended raw materials. For example, when using a resin in which two types of resin a and resin b are alloyed so that the ratio of resin a is higher, resin a is defined as the thermoplastic resin described in this invention. When the two are blended in a ratio of exactly 50:50, both resin a and resin b are considered to be the main components.
[0034] The laminated film of the present invention preferably has a structure in which 9 or more layers of A and B are alternately laminated. By using a film having such a laminated structure, a structure is formed in which polymer molecules are likely to respond in the in-plane direction of the film during the manufacturing process, and further, the laminated resin interface is aligned in the in-plane direction, so that a material with high shape recovery function and little residual tensile strain can be obtained. In addition, since a highly rigid resin that controls shape fixation and a resin that shows elastic stretchability exist independently, the shape fixation ability can be improved compared to a single-layer film material using a conventional kneaded and dispersed polymer.
[0035] In the present invention, alternate lamination refers to the fact that the thermoplastic resin A constituting the A layer and the thermoplastic resin B constituting the B layer are laminated in a regular arrangement in the thickness direction, and refers to a state in which the resins are laminated according to a regular arrangement of A(BA)n (n is a natural number), B(AB)n (n is a natural number), or (AB)n (n is a natural number). When producing a laminated film having the configuration of A(BA)n or B(AB)n, a plurality of resins, namely, thermoplastic resin A and thermoplastic resin B, are sent out from different flow paths using two or more extruders, and a multi-manifold type feed block or a square mixer, which is a known lamination device, can be used. In particular, in order to efficiently obtain the configuration of the present invention, a method using a feed block having fine slits is preferable because it realizes high-precision lamination and improves the shape fixing and shape restoration properties. In the case of the square mixer method, the number of layers can be easily doubled by dividing the molten laminate flowing in the polymer pipe in the middle and overlapping the halves of the molten laminate while stretching each half. However, the cross-sectional area of the flow path through which the resin flows changes during the process from division to merging, which may cause the laminate state to collapse and cause lamination disorder. This may result in the shape fixation / restoration properties that should be obtained with the same number of layers not being obtained. When forming a laminate unit using a slit-type feed block, the thickness and distribution of each layer can be achieved by changing the length and width of the slit to gradient the pressure loss. The length of the slit is the length of the comb teeth that form the flow path for flowing layers A and B alternately in the slit plate. In the case of B(AB)n (n is a natural number), it is sufficient to interpret it by exchanging thermoplastic resin A and thermoplastic resin B. Therefore, in the following, the laminate film will be described as having a configuration of A(BA)n (n is a natural number).
[0036] Of the structures A(BA)n and (AB)n, the structure A(BA)n is more preferable. By forming both outermost layers from the same layer, the laminated film can be produced by the same production method as that for the monolayer film made of the thermoplastic resin.
[0037] Furthermore, as the arrangement of the thermoplastic resin for the structure in which the A layer and the B layer are alternately laminated, the A layer and the B layer are alternately arranged, and an intermediate layer (C layer) adjacent to both layers is arranged, such as an (ACBC)n structure or (ACB)nA structure, or a laminate structure such as C(AB)nC having an (AB)n regular arrangement and a different layer on the outermost layer can be used. In this case, it is preferable that the A layer and the B layer are alternately included in 9 layers. By including this regular arrangement, the thermoplastic resin constituting the C layer is selected to have an intermediate element compatible with both the thermoplastic resin A constituting the A layer and the thermoplastic resin constituting the B layer, thereby increasing the interlayer adhesion of the laminate film, and making it possible to obtain a laminate film that can be used repeatedly for a long period of time.
[0038] In the laminated film of the present invention, the presence of multiple thermoplastic resins is determined by the definition of the "different" thermoplastic resin layers. As described below, A layer, B layer, C layer, etc. are defined according to the thermal properties of each layer, but considering the possibility of a measurement error between the thermal properties obtained from the entire laminated film and the thermal properties measured for each resin layer, the layer whose melting point is ±5°C of the highest melting point Tm of the laminated film is defined as A layer, the layer whose glass transition temperature or melting point, whichever is higher, is ±5°C of Tn of the laminated film is defined as B layer, and the other layers are defined as C layer, D layer, etc. in order of increasing glass transition temperature. In addition, according to the above definition, it is preferable that the melting point Tm and the shape conversion point Tn described below are Tm-Tn>5°C by definition.
[0039] In addition, although each layer is made of a polymer whose main component is a "different" thermoplastic resin, if the melting point of each layer is within ±5°C of the highest melting point Tm of the laminated film, the layer with the greater number of layers is called Layer A, and the layer with the fewer number of layers is called Layer C, Layer D, etc. The same applies to Layer B.
[0040] In addition, the laminated film of the present invention may be provided with a hard coat layer, an easy adhesion layer, a gas barrier layer, an adhesive layer, a peeling layer, etc., separately on at least one side as a functional layer on the outermost surface of the laminated structure showing the regular arrangement of A(BA)n. In particular, as described later, the laminated film of the present invention is preferably a thermoplastic elastomer resin that is crystalline and can exhibit elastic stretching behavior as the thermoplastic resin A constituting the A layer, which is the surface layer of the laminated film, but such a resin may be insufficiently cooled in the casting process, exhibit tackiness to a normal metal roll, and not peeled off, causing a problem of the laminated film wrapping around the roll. In order to improve the cast peelability, a method of eliminating tackiness may be considered, such as changing the roll material to one that matches the surface layer polymer, or coating the cast drum surface with a release agent or release treatment, but the effect may decrease over time, or the component may remain on the surface of the laminated film, affecting the physical properties of the laminated film. Therefore, a method of stabilizing the casting process by laminating a thermoplastic resin that does not exhibit tackiness to a metal roll and can be peeled off from the laminated film showing the elastic stretching behavior later on the outermost layer as a peeling layer by coextrusion can be suitably used. However, the judgment of the thermoplastic resins that are "alternately laminated" as described in the present invention is limited to the portions that show a regular arrangement.
[0041] In the laminated film of the present invention, the thermoplastic resin A mainly used in the A layer arranged in the outermost layer is preferably a crystalline resin. By using a crystalline resin, it is possible to obtain a good molded product with less thickness unevenness and molding (stretching) unevenness, and the laminated film becomes a material with excellent heat resistance and durability due to the effect of the crystalline resin arranged in the outermost layer, and can be handled in the same manner as a single-layer film material using a crystalline resin. Therefore, it is preferable that the outermost layers on both sides of the laminated film are crystalline resins, and further, in order to fully exert the shape fixation / restoration of the present invention, they are crystalline thermoplastic elastomer resins that exhibit rubber elasticity behavior. In addition, since the basic shape that is restored after reheating the laminated film of the present invention is a shape formed at a temperature near the melting point, the basic shape of the material to be transformed is given at a temperature equal to or higher than the melting point of the crystalline resin.
[0042] Among the thermoplastic elastomers, the thermoplastic resin A is preferably selected from any of polystyrene, polyester, polyurethane, and polyamide resins from the viewpoints of versatility, flex resistance, and strength. Furthermore, from the viewpoints of the resistance to deformation strain of the laminated film after deformation / restoration cycles and weather resistance, it is more preferable that the thermoplastic resin A is one selected from the group consisting of polyurethane, polyester, and polyamide resins. Furthermore, from the viewpoints of film formability by melt extrusion and heat resistance, it is preferable that the thermoplastic resin A is polyester or polyamide. By selecting these resins, the range of types of thermoplastic resins that can be selected according to the desired shape transformation temperature is expanded, and the applicable temperature range as a shape fixing / restoring material can be expanded. On the other hand, in the case of tape applications described later, since it is used in close contact with the human body for a long time, water vapor permeability to a degree that does not interfere with skin breathing may be required. When used for such applications, it is preferable to select from polyurethane-based and polyamide-based resins.
[0043] The laminated film of the present invention preferably includes a structure in which an A layer mainly made of a thermoplastic resin A and a B layer mainly made of a thermoplastic resin B different from the thermoplastic resin A are alternately laminated in 9 or more layers. By increasing the number of layers contained in the laminated film, the layer made of the thermoplastic resin softened at a certain temperature or higher is more likely to follow the deformation of the adjacent thermoplastic elastomer resin exhibiting crystalline elastic behavior and to respond mechanically. If the number of layers is less than 9, the thickness of each layer constituting the laminated film is large, so that the softened thermoplastic resin layer does not sufficiently deform and respond mechanically to follow the behavior of the adjacent thermoplastic elastomer resin, and the response of shape deformation / restoration may be reduced. More preferably, the number of layers is 51 layers or more, even more preferably, 101 layers or more, and particularly preferably, 301 layers or more. Although there is no upper limit to the number of layers, as the number of layers increases, problems such as an increase in manufacturing costs due to the increase in the size of the manufacturing equipment and a tendency for lamination disorder to occur due to the non-Newtonian viscosity behavior of the elastic elastomer resin arise, so that in reality, the practical range is 1000 layers or less.
[0044] The laminated film of the present invention preferably has two or more loss tangent (tan δ) peaks when dynamic viscoelasticity measurement is performed at a frequency of 10 Hz for a temperature range from -80°C to Tm, and the relationship between the tan δ peak tan δ1 occurring at the lowest temperature (temperature T1 (°C)) and the tan δ peak tan δ2 occurring at the highest temperature (temperature T2 (°C)) is tan δ2 / tan δ1 ≧ 1.0. The loss tangent mentioned here can be expressed as the ratio of the loss modulus (G'') to the storage modulus (G') when dynamic viscoelasticity measurement is performed on the laminated film at the above-mentioned frequency, and indicates a temperature range where the energy absorption amount of the laminated film is large, that is, a temperature range where the viscoelastic change of the material is more significant. The temperature where the viscoelastic change is significant generally corresponds to the temperature at which the phase transition occurs between the glass state, the rubber state, and the molten state, such as the glass transition temperature or melting point of the thermoplastic resin constituting the material.
[0045] An example of a loss tangent spectrum in dynamic viscoelasticity measurement obtained for the laminated film of the present invention is shown in Figure 2. In Figure 2, reference numeral 4 denotes the loss tangent tan δ spectrum obtained in dynamic viscoelasticity measurement, reference numeral 5 denotes temperature T1 [°C], reference numeral 6 denotes the loss tangent peak occurring at the lowest temperature, reference numeral 7 denotes temperature T2 [°C], reference numeral 8 denotes the loss tangent peak occurring on the highest temperature side in the temperature range lower than the melting point Tm, reference numeral 9 denotes tan δ1, reference numeral 10 denotes tan δ2, and reference numeral 11 denotes the loss tangent peak occurring at a temperature different from temperatures T1 and T2.
[0046] In addition, although not shown in the figure, there are cases where the tan δ peaks are close to each other and overlap with each other, resulting in some spectra being obtained as shoulder peaks rather than clearly independent peaks with peak tops. In such cases, the spectrum slope at each temperature is calculated by differential analysis of the obtained tan δ spectrum, and the temperature at which the slope is greatest when the slope changes from a decreasing trend to an increasing trend and then to a decreasing trend, or the temperature at which the slope is greatest when the slope changes from an increasing trend to a decreasing trend and then to an increasing trend, is defined as the temperature corresponding to the shoulder peak.
[0047] In a laminated film made of a plurality of different thermoplastic resins as in the present invention, if the melting point Tm is derived from a crystalline thermoplastic resin A, in the temperature range lower than the melting point Tm, in addition to the glass transition temperature derived from the thermoplastic resin A, if the thermoplastic resin B is an amorphous resin, a tan δ peak will appear at the glass transition temperature, and if it is a crystalline resin, a tan δ peak will appear at the temperature corresponding to the glass transition temperature and the melting point, and at least two or more loss tangent peaks will appear. In a single-layer film using a conventional kneaded and dispersed polymer, if the compatibility of the two types of thermoplastic resins to be combined is good and both resins are well finely dispersed, the material behaves as a single resin material macroscopically, and only one tan δ peak appears at the glass transition temperature other than the melting point, so the number of tan δ peaks does not apply. In other words, this tendency can be confirmed characteristically in a material that shows a sea-island structure due to poor dispersion or in a multilayer laminated film as in the present invention.
[0048] However, if the two thermoplastic resins are not sufficiently dispersed, the shape fixing / restoring ability of the resulting laminated sheet is completely separated as a tan δ peak, but the shape fixing / restoring ability of the resulting laminated sheet depends on the resin mixing ratio and the resulting mixed polymer composition and properties, and the magnitude of the tan δ peak also changes to represent the properties. Specifically, if the mixing ratio is designed so that the amount of polymer components such as thermoplastic elastomer resins with strong elastic stretching behavior is large, the material becomes easy to restore its shape, and the tan δ spectrum obtained from the dynamic viscoelasticity measurement also has the largest tan δ peak at a temperature that coincides with the low glass transition temperature of the thermoplastic elastomer. Since it is necessary for the thermoplastic elastomer to always exhibit rubber elastic behavior at temperatures around the target room temperature, the thermoplastic elastomer exhibits a glass transition temperature at a temperature lower than the glass transition temperature of the other thermoplastic resin with high rigidity, and in the laminated film of the present invention, the tan δ1 obtained at the temperature T1, which is the lowest temperature in the temperature range lower than the melting point Tm, is the peak with the highest tan δ. It is preferable that such a temperature T1 exists at a temperature below room temperature and below 0°C as much as possible.
[0049] On the other hand, polymers designed to have a high content of highly rigid thermoplastic polymers are materials with excellent shape fixing ability, and the tan δ spectrum obtained from dynamic viscoelasticity measurement also has the largest tan δ at the temperature corresponding to the softening point or melting point of the highly rigid thermoplastic resin. In such materials, the material exhibits shape fixing / restoring properties due to the switching between solidification and softening of the rigid thermoplastic resin, so that the highest tan δ2 peaks at tan δ at the highest temperature T2 in the temperature range below the melting point, which corresponds to the melting point for crystalline resins and the glass transition temperature for amorphous resins, where the resin exhibits softening properties.
[0050] However, as described in the background section, such a resin kneaded with multiple resins can be made into a material specialized for shape fixation or shape recovery, but it is difficult to make it into a material that combines both properties. Therefore, in the present invention, by designing these multiple thermoplastic resins to behave as individual polymer layers by alternately laminating them, the laminated structure does not collapse significantly even if the ratio of the two resins is changed, so that shape fixation / shape recovery due to mechanical response in the layer direction can be expressed regardless of the lamination ratio, and compared to the technology using conventional kneaded resins, it has become possible to adjust the desired shape fixity and shape recovery properties by the lamination ratio while maintaining high shape fixation / recovery properties. Note that even in the case of a multi-layer laminate structure, the approach to the tendency of tan δ peaks in thermal properties and viscoelastic properties can be interpreted as being the same as that of the monolayer film made of the conventional kneaded resin described above.
[0051] In the laminated film of the present invention, among the two or more loss tangent peaks that appear, when the peak that appears at the lowest temperature (temperature T1 ° C) in the temperature range of -80 ° C or more and less than the melting point Tm is tan δ1 and the peak that appears at the highest temperature (temperature T2 ° C) is tan δ2 / tan δ1 ≧ 1.0 is preferable. Temperature T2 corresponds to the shape change point Tn of the laminated film in the description of the differential calorimeter measurement, and corresponds to the glass transition temperature (in the case of an amorphous resin) or melting point (in the case of a crystalline resin) derived from thermoplastic resin B. Temperature T1 is the temperature that appears at the lowest temperature and indicates the glass transition temperature of thermoplastic resin A or B. In particular, considering the preferred thermoplastic resin configuration of the laminated film of the present invention, that is, thermoplastic resin A is a crystalline thermoplastic elastomer and thermoplastic resin B is an amorphous or crystalline thermoplastic resin, temperature T1 generally corresponds to the glass transition temperature derived from thermoplastic resin A due to the characteristics of the resin used. The spectrum corresponding to reference symbol 11 depends on the crystallinity of the thermoplastic resin used, and therefore often does not exist when an amorphous resin is used as a resin with high rigidity.
[0052] Among the multiple tan δ peaks thus appearing, the tan δ peak position with the highest peak intensity indicates the most characteristic phase transition state of the laminate film. However, since the laminate film of the present invention is characterized by being a material that converts between shape fixation and shape change / restoration functions, and further by having high strength of the entire laminate film, it is preferable that tan δ at temperature T2, which corresponds to the temperature at which the physical properties change due to the highly rigid thermoplastic resin, shows the highest peak intensity and shows tan δ2 / tan δ1≧1.0. More preferably, it is 3.0 or more, and even more preferably 4.0 or more. When tan δ2 / tan δ1 shows less than 1, it indicates that the laminate film is strongly influenced by the elastic behavior derived from thermoplastic resin A (thermoplastic elastomer), and therefore the material has strong elastic shrinkage behavior as a laminate film and does not sufficiently obtain shape fixation / restoration function at temperature T2. Therefore, the strength of the entire laminate film may also be inferior. In order to achieve tan δ2 / tan δ1≧1.0, it can be achieved by a laminate film with a large number of layers in a multilayer laminate structure, a laminate film without lamination disorder, thermoplastic resin B being an amorphous resin, and a small lamination ratio and a large amount of amorphous resin components.
[0053] The laminated film of the present invention preferably has a lamination ratio of 0.3 or more and 1.5 or less. In accordance with the preferred design in which the thermoplastic elastomer is arranged in the outermost layer, the lamination ratio is defined as the ratio of the thickness of the A layer including the outermost layer to the B layer made of a highly rigid thermoplastic resin. When the lamination ratio exceeds 1.5, the influence of the elastic behavior of the thermoplastic elastomer may be high even in the case of a laminated film, and when the lamination ratio is below 0.3, the influence of the highly rigid B layer may become dominant, resulting in a decrease in the shape recovery force. In order to combine the shape fixation / recovery ability of the laminated film at a specific temperature with the strength of the laminated film at room temperature, it is preferable that the ratio of the highly rigid thermoplastic resin constituting the laminated film is relatively high, and the lamination ratio is more preferably 0.3 or more and 1.0 or less. The lamination ratio can be adjusted by the discharge ratio of the extruder that supplies different thermoplastic resins. At this time, the discharge ratio and the thickness ratio may be affected by the polymer density and therefore may have different numerical values in the strict sense, and should be appropriately adjusted taking into account the resin density according to the type of thermoplastic resin.
[0054] In the laminated film of the present invention, when the loss tangent of layer A at temperature T (°C) is tanδA(T) and the loss tangent of layer B is tanδB(T), it is preferable that tanδA(T1)>tanδB(T1) and tanδA(T2)<tanδB(T2). The tanδ of each layer can be determined by analyzing the storage elastic modulus and loss elastic modulus of each layer at a desired temperature by AFM tapping measurement described in the measurement method section below, and calculating the loss tangent from the ratio of the loss elastic modulus to the storage elastic modulus. This is an important condition for exhibiting the shape fixing / restoring characteristics aimed at by the present invention. It can be achieved by using a thermoplastic resin, preferably a thermoplastic elastomer, that exhibits elastic stretching and contracting behavior at room temperature to the use temperature, and by a suitable design that switches solidification (shape fixing) and softening (shape deformation / restoring) at the glass transition temperature or melting point of the other highly rigid thermoplastic resin. Therefore, in layer A made of a crystalline thermoplastic elastomer having a glass transition temperature below room temperature, the tanδ peak at temperature T1 is particularly large, and the tanδ peak at temperature T2 that controls shape fixing / deformation / shape restoration is particularly high in layer B made of the other highly rigid thermoplastic resin B. If tanδA(T1)≦tanδB(T1) or tanδA(T2)≧tanδB(T2) is shown, it indicates that the thermoplastic elastomer exhibiting elastic stretching and contracting behavior is thermoplastic resin B, which means that a thermoplastic resin exhibiting rigidity is used for layer A. When the resin is an amorphous resin, it may be inferior in terms of adhesion to the mold or roll during molding and the heat resistance and durability of the laminated film. When the resin is a crystalline resin, sufficient rigidity may not be exhibited until the melting point is reached, and the elastic stretching and contracting behavior of the thermoplastic elastomer may not be fully expressed. When a crystalline and elastic resin is used, the shape fixing ability may decrease because both resins exhibit elastic contraction behavior.
[0055] In the laminate film of the present invention, when Tn is a glass transition temperature or melting point appearing in a region lower than the highest melting point Tm obtained by the differential scanning calorimeter measurement, it is preferable that the permanent strain when a 50% strain is applied at Tn+20°C is 20% or less.
[0056] The thermal properties obtained when the laminate film of the present invention is analyzed by differential scanning calorimetry will be described with reference to Figs.
[0057] Fig. 3 shows a schematic diagram of a differential calorimeter spectrum of a laminated film using a crystalline thermoplastic elastomer as one thermoplastic resin and an amorphous thermoplastic resin showing a glass transition temperature at a temperature Tn as the other thermoplastic resin. In the case of such a configuration, the melting point Tm derived from the crystalline thermoplastic elastomer appears as an endothermic peak indicated by reference numeral 15, the glass transition temperature Tn appearing in a region lower than the melting point Tm as a step region indicated by reference numeral 14, and the glass transition temperature appearing in an even lower temperature region indicated by reference numeral 13. Here, the crystalline thermoplastic elastomer can show stretching behavior as a rubber-like region in the temperature range indicated by reference numeral 16 from the glass transition temperature of the resin to the melting point Tm.
[0058] Here, it is preferable that the glass transition temperature of the amorphous thermoplastic resin coincides with T2 at which a peak appears in the dynamic viscoelasticity measurement. If the glass transition temperature of the amorphous thermoplastic resin is the lowest glass transition temperature indicated by reference numeral 13, the thermoplastic resin B is always substantially in a molten state in a temperature range above that temperature, and the deformation caused by the thermoplastic elastomer cannot be sufficiently maintained, and there may be a problem that the deformation during molding becomes non-uniform. For this reason, it is preferable to design the amorphous thermoplastic resin to have a glass transition temperature, and to switch between solidification and melting around that temperature, thereby allowing control of shape deformation, fixation, and restoration.
[0059] In light of the above, it is preferable that the laminated film of the present invention is designed such that the glass transition temperature of the thermoplastic resin A exhibiting elastic stretch behavior, the glass transition temperature of the amorphous thermoplastic resin B, and the melting point of the thermoplastic resin A are arranged in this order. At this time, the temperature range exceeding the glass transition temperature of the thermoplastic resin A and lower than the glass transition temperature of the thermoplastic resin B is the temperature region in which the shape of the laminated film is fixed by the rigidity exhibited by the thermoplastic resin B, and the temperature range is preferably 30°C or more and less than 200°C. Furthermore, the temperature range exceeding the glass transition temperature of the thermoplastic resin B and lower than the glass transition temperature of the thermoplastic resin A is the region in which the laminated film can exhibit shape deformation and shape recovery characteristics, and the temperature range is preferably 30°C or more and 250°C or less. These temperatures can be appropriately set according to the functions required for the laminated film of the present invention.
[0060] FIG. 4 shows a schematic diagram of the differential calorimetry spectrum of a laminated film using a crystalline thermoplastic elastomer as one thermoplastic resin and a highly rigid crystalline thermoplastic resin as the other thermoplastic resin. In this case, the melting point of the highly rigid crystalline thermoplastic resin appears as reference numeral 14, and the elasticity of the thermoplastic elastomer can be expressed or stopped by switching between the rubber-like region and the molten state. There are two cases where the glass transition temperature appears in a lower temperature region, reference numerals 13 and 17, and this should be set appropriately according to the type of thermoplastic resin. However, the thermoplastic elastomer A is the resin that shows the glass transition temperature (corresponding to reference numeral 13) at the lowest temperature, and the resin composition is functionally separated between the elastic resin and the highly rigid resin, which is suitable for enhancing the shape fixation / restoration properties and temperature responsiveness of the present invention.
[0061] In the case of the above laminated film configuration, it is preferable to design the laminated film so that the glass transition temperature of the thermoplastic resin A exhibiting elastic stretch behavior, the melting point of the highly rigid crystalline thermoplastic resin B, and the melting point of the thermoplastic resin A are arranged in this order. At this time, the temperature range exceeding the glass transition temperature of the thermoplastic resin A and lower than the melting point of the thermoplastic resin B is the temperature region in which the shape of the laminated film is fixed by the rigidity exhibited by the thermoplastic resin B, and the temperature range is preferably 30°C or more and less than 200°C. Furthermore, the temperature range exceeding the melting point of the thermoplastic resin B and lower than the melting point of the thermoplastic resin A is the region in which the laminated film can exhibit shape deformation and shape recovery characteristics, and the temperature range is preferably 30°C or more and 250°C or less. These temperatures can be appropriately set according to the functions required for the laminated film of the present invention.
[0062] The thermoplastic resin (thermoplastic resin B) different from the thermoplastic elastomer is preferably an amorphous thermoplastic resin as shown in the former. As a result, in the latter case where an elastic resin is used as a crystalline thermoplastic resin, the resin may not be completely solidified at a temperature lower than the melting point of the resin, and may exhibit rubber elastic behavior in a temperature range up to the glass transition temperature. In this case, the thermoplastic resin B may not be able to completely control the ON / OFF of the stretching behavior of the thermoplastic elastomer, and the dimensional fixation rate of the laminated film may be reduced. Therefore, it is preferable that the thermoplastic resin B is an amorphous thermoplastic resin that can cause a large change in elastic modulus due to solidification / melting of the thermoplastic resin B and bring about a large change in elastic modulus relative to the elastic modulus of the thermoplastic elastomer. From the above, it is particularly preferable that the thermoplastic resin B is an amorphous thermoplastic resin that exhibits a glass transition temperature Tn.
[0063] Applying 50% strain at a temperature of Tn+20℃ refers to repeatedly performing a "50% stretching-reheating cycle test" at Tn+20℃. Specifically, as will be explained in detail in the measurement method section below, a Bruckner KARO-V sheet stretcher is used to perform uniaxial stretching of a certain length sample at Tn+20℃ by 1.5 times (50% strain), and the film is cooled and solidified until the film temperature is displayed as a film temperature below Tn. The stretched sample is then left to stand (reheated) for 1 minute under no load in a hot air oven at Tn+20℃. By repeating this process, the thermoplastic resin that constitutes the laminated film accumulates strain due to molecular structure changes and structural destruction (crystal structure cleavage), but the structure gradually stabilizes and the amount of strain increase decreases with each cycle test. The dimensional change rate based on the dimensions before the cycle test at the point when the dimensional recovery before and after the cycle test is finally 100% is defined as the permanent strain according to the following formula (2). In calculating permanent set, since it is laborious to perform the test until the dimensional change is completely eliminated, for convenience, the above cycle test is performed at least five times, and the calculation is based on the data obtained from the curve 18 that exponentially approximates the dimensional change after the cycle test, as shown in Figure 5. Here, the sample length before the test is d, and the sample length after the test when the dimensional recovery rate is 100% is d. ∞ Shown as:
[0064]
number
[0065] The permanent strain thus obtained is preferably 20% or less, more preferably 15% or less, and even more preferably 10% or less. By forming a laminated film showing such a low permanent strain, the material is less deformed even when used repeatedly, and it can be said to be a shape fixing / restoring material that is resistant to multiple uses and can be used for a long period of time. In order to reduce the permanent strain in this way, it can be achieved by using an amorphous resin as the thermoplastic resin B and increasing its lamination ratio, or by selecting one or more types selected from polyurethane, polyester, and polyamide resins as the thermoplastic elastomer.
[0066] In the laminated film of the present invention, it is preferable that the inflection point in differential analysis appears for the first time in a region of 50% or more strain in the strain-stress curve in a tensile test at Tn+20° C. With regard to the strain-stress curve, a schematic diagram of the strain-stress curve when stretched at a temperature below Tn is shown in FIG 6, and a schematic diagram of the strain-stress curve when stretched at a temperature of Tn+20° C. is shown in FIG 7. Reference numeral 20 denotes the strain-stress curve in the tensile test, reference numeral 21 denotes the inflection point (upper yield point) in differential analysis, and reference numeral 22 denotes the magnitude of the upper yield point strain.
[0067] In the tensile test of laminated film, in addition to the stretching conditions of the laminated film (elongation and tension), physical property information such as the elongation of the laminated film that undergoes plastic deformation and remains as distortion can be obtained. Under temperature conditions (below temperature Tn [℃]) when the laminated film is not softened, that is, when the thermoplastic resins that make up the laminated film are not softened (in a glassy state), the unsoftened thermoplastic resin is forcibly stretched, and the stress rises at a small stretch ratio, causing an upper yield point strain (symbol 21), and even if the film shrinks by the amount of the strain, it cannot restore to its original shape. On the other hand, under temperature conditions (above temperature Tn) when all the thermoplastic resins that make up the laminated film soften, the thermoplastic resins can smoothly follow while changing their structure, making it possible to deform the material in a state where distortion is unlikely to remain. The point at which plastic deformation begins (referred to as the upper yield point) corresponds to the convex peak position (reference numeral 21) where the stress first increases after the start of stretching in the strain-stress curve obtained in the tensile test, and can be grasped by performing differential analysis of the obtained curve and analyzing the so-called inflection point where the slope of the peak changes from positive to negative. Thus, it is important for the shape-fixing / restoring material of the present invention that the elongation showing the upper yield point strain is high and the material can be restored to its original state.
[0068] In the laminated film of the present invention, it is preferable that the inflection point (upper yield point) occurs at 50% or more. As described later, this laminated film can be preferably used as a sheet material for medical, household, and industrial applications. However, when it is used in industrial applications by following the shaping of a complex shape, or in medical or household applications by stretching and contracting in a complex shape such as a movable part of a complex human body, a certain degree of elongation is required. Particularly in medical applications, an elongation of about 20 to 30% is required even outside the joint parts of the limbs, and an elongation of up to about 60 to 70% is applied around the joints. Therefore, it is preferable that elastic deformation occurs without plastic deformation up to these elongation regions. From this viewpoint, the inflection point appearing in the strain-stress curve is more preferably in the region of 60% or more, and even more preferably 65% or more. In order for the inflection point to appear in the region where the strain is 50% or more, while having a multi-layer laminated structure of 9 layers or more, the number of laminated layers is large, the thermoplastic elastomer used has a low crystallinity and is a resin in which permanent strain hardly remains, an amorphous thermoplastic resin B that is less likely to affect the strain is used, or the lamination ratio is designed to be low so that the ratio of the thermoplastic resin B increases.
[0069] When the storage elastic modulus of the A layer at the temperature T (°C) is GA(T) (MPa) and the storage elastic modulus of the B layer is GB(T) (MPa) in the laminated film of the present invention, it is preferable to satisfy 1.2GA(Tn - 10) < GB(Tn - 10) and GA(Tn + 10) ≥ 1.2GB(Tn + 10) with respect to the above temperature Tn.
[0070] The shape change / restoration function, which is a characteristic feature of the laminated film of the present invention, can be realized by using a multi-layer laminate structure as the basic structure, and by using a material in which a polymer with strong elasticity and a polymer with high rigidity are alternately laminated, and by designing the relationship between the elastic moduli of the two polymers to change around a specific temperature. Since the two types of polymers that are the constituent components and exhibit different viscoelasticity behave within the material as completely independent polymer layers, unlike conventional single-film film technology, it is possible to exhibit high shape fixation and shape restoration amounts in response to deformation in a specific direction without depending on the combination or ratio of the two types of polymers. Specifically, the shape fixation / restoration property can be expressed by switching the function of thermoplastic resin B, which switches from a rigid state to a molten state or a rubber elastic state at the boundary temperature of the conversion temperature Tn, as a stopper against the rubber elastic shrinkage behavior of thermoplastic resin A. The realization of this shrinkage switching function is obtained by the relationship between the storage moduli of the thermoplastic resins that make up the laminated film. In other words, in the temperature range lower than the temperature Tn, the storage modulus of thermoplastic resin B, which exhibits rigidity in a glass state, is significantly higher than that of thermoplastic resin A, which can exhibit elastic stretch behavior, and the shape can be fixed by repelling the elastic stretch behavior of thermoplastic resin A. On the other hand, in the temperature range higher than the temperature Tn, thermoplastic resin A exhibits elastic expansion and contraction behavior, while thermoplastic resin B exhibits molten or rubber-like behavior and its elastic modulus becomes low, so that the contraction of thermoplastic resin A automatically restores the shape, and the desired shape can be given by applying an external force. However, since this conversion of mechanical behavior does not change dramatically at the temperature Tn, the difference in elastic modulus in the temperature ranges of Tn-10°C and Tn+10°C is specified here. The storage elastic modulus of each layer in the laminated state is obtained by the peak force tapping method of an atomic force microscope (AFM) for the cross section of the laminated film. Specifically, a silicon cantilever is moved vertically, and the elastic modulus of each thermoplastic resin layer is analyzed based on the obtained force curve by repeatedly pressing it against the cross section and releasing it.
[0071] Under the temperature condition where the shape fixing function works at Tn-10°C, the storage modulus GB(Tn-10) of the thermoplastic resin B layer is preferably greater than 1.2 times the storage modulus GA(Tn-10) of the thermoplastic resin A. If the difference in modulus is not greater than 1.2 times, the thermoplastic resin B cannot suppress the elastic shrinkage behavior of the thermoplastic resin A, and therefore, after the shape is changed and the stress is released, the shrinkage caused by the thermoplastic resin A acts, resulting in a problem of a decrease in the dimensional fixation rate. In order to increase the shape fixing ability from the viewpoint of the resin properties, the difference is more preferably 4.0 times or more, and even more preferably 10 times or more.
[0072] On the other hand, at the temperature condition Tn+10°C that contributes to shape imparting and shape restoration, it is preferable that the storage modulus GA(Tn+10) of the thermoplastic resin A layer is greater than 1.2 times the storage modulus GB(Tn+10) of the thermoplastic resin B so that the laminated film can easily deform with low stress. If the elastic modulus of the thermoplastic resin A at that temperature is lower than 1.2 times, the repulsion against the shape change caused by the thermoplastic resin B during deformation is strong, so that the material is forcibly deformed during molding, and permanent distortion is likely to remain in the material. In addition, if the elastic modulus difference is small, it is considered that both thermoplastic resins are in a similar polymer state, especially a rubber-like state, and the dimensional fixation rate may be low. In order to increase the shape restoration ability of the thermoplastic resin B, it is more preferably 2.0 times or more, and even more preferably 3.0 times or more. All of these are derived from the characteristics of the thermoplastic resin, and it is important to select a thermoplastic resin that exhibits the desired elastic modulus, but in order to increase the elastic modulus difference in order to fully exert the shape fixing ability, it can be achieved by selecting an amorphous resin as the thermoplastic resin B.
[0073] In the laminated film of the present invention, it is preferable that the Tm and Tn satisfy Tm-Tn≧30°C. Tm-Tn as described here refers to the temperature range from the melting point of the crystalline resin to the shape conversion point, and indicates the temperature range in which shape change and shape restoration are possible since the thermoplastic resin A exhibits rubber elastic behavior while the thermoplastic resin B is softened or melted. The small temperature range may cause the laminated film to show a sheet shape but not be able to fully exhibit the shape restoration function, since the resin melts before the shape restoration due to the contraction of the thermoplastic resin A is completed at a temperature exceeding the shape conversion point Tn. Therefore, in order to obtain a laminated film with a shape restoration function, it is preferable to keep the temperature range from the shape conversion point Tn to the melting point Tm of the crystalline thermoplastic resin A constituting the laminated film as large as possible, more preferably 50°C or more, and even more preferably 85°C or more. This is due only to the resin characteristics, and can be achieved by selecting the melting point and glass transition temperature of the thermoplastic resin to be laminated in consideration of the melting point.
[0074] The laminated film of the present invention preferably has a property such that the dimensional fixation rate after stretching is 90% or more in the fifth test when a 50% stretch forming-reheating cycle test is repeated five times at Tn+20° C. Here, when the sample length before the test is d and the sample length after uniaxial stretching + cooling and solidification is d', the dimensional fixation rate after 50% stretching can be expressed by formula (3).
[0075]
number
[0076] The dimensional fixation rate is a quantification of the ability to maintain the desired shape without shrinking back after stretching it into shape, and a large value indicates that the material can be used while maintaining the desired shape. Each time the stretching process is repeated, the polymer molecular structure transformation associated with stretching becomes less likely to occur, and the molecular structure shown for each shape change is stable when the same amount of shape change is repeated, so the value tends to increase with the number of cycle tests. Among them, a dimensional fixation rate of over 90% is preferable as a shape-fixing material that is used repeatedly, even when the permanent deformation of the material is taken into consideration, and a sufficiently high shape fixing ability of the material leads to, for example, in the case of medical plaster, the fixation is strong, improving the healing ability, and in the case of sensor use, the desired amount of change is obtained, which leads to improved function as a sensor. More preferably, it is 95% or more, and even more preferably 99%. Since molecular structure transformation during repeated tests is likely to occur due to crystalline components in the molecular structure, this can be achieved by having a small amount of crystalline components in the laminate film as a whole. In other words, the lamination ratio of thermoplastic resin B, which contributes to fixing the dimensions, is large (the ratio of the total thickness of layer A, whose main component is thermoplastic resin A, to the total thickness of layer B, whose main component is thermoplastic resin B, is small) and an amorphous resin is used as thermoplastic resin B.
[0077] On the other hand, when the dimensional recovery rate is calculated from the amount of dimensional change before and after a series of cycle tests, it is preferable that the dimensional recovery rate after the fifth cycle test is 80% or more. The dimensional recovery rate is a numerical value that quantitatively indicates how much a material shaped into a desired shape returns to its original shape when heated again, and a large numerical value indicates that the material can be used repeatedly with the same properties by returning to its original shape. As a result of the molecular structure transformation caused by the cycle test, the dimensions tend to expand and generally deteriorate with each cycle of shape deformation compared to the initial dimensions before the test. Therefore, a high dimensional recovery rate indicates the repeated characteristics as a shape fixing / restoring material, so a high numerical value is preferable. Here, the dimensions after the fifth test are measured based on the dimensions before the first cycle test, and the dimensional recovery rate after the fifth test is calculated. More preferably, it is 90% or more, and even more preferably, it is 95% or more. In order to increase the shape recovery rate even in repeated tests, it is preferable to select a resin that is less likely to develop a crystal structure and has small permanent deformation as the thermoplastic elastomer resin. Specifically, it is preferable to select from polystyrene-based elastomer resins, polyester-based elastomer resins, amide-based elastomer resins, etc. In addition, as the lamination ratio of two types of thermoplastic resins, a high ratio of thermoplastic resin A exhibiting elastic stretch behavior that tends to leave permanent strain after processing, and a high ratio of thermoplastic resin B with high rigidity are both causes of reduced dimensional recovery, so it is easy to achieve this by setting the lamination ratio range to 0.3 or more and 3.0 or less. More preferably, it is 0.3 or more and 1.5 or less, and even more preferably, it is 0.3 or more and 1.0 or less.
[0078] The laminate film of the present invention is preferably a laminate film that can be used in applications requiring shape fixing and shape recovery properties. More specifically, the laminate film can be suitably used in applications requiring the ability to fix (retain) a shape, such as a bent shape, at a temperature equal to or lower than the Tn and to restore the fixed shape at a temperature exceeding the Tn.
[0079] Specifically, the laminated film of the present invention can be suitably used in various applications requiring particularly high flexibility and stretchability, taking advantage of its excellent flexibility, stretch response, and heat resistance. For example, it can be suitably used for electronic device materials such as smartphone housings, touch panels, color filters, flat panel displays, flexible displays, flexible devices, wearable / wearless devices, and sensors, in-vehicle materials such as mirrors, window members, dashboards, car navigation touch panels, room mirrors, and windows, and for various printed materials, medical films, sanitary material films, agricultural films, building material films, clothing materials, and the like, as surface materials, internal materials, constituent materials, and manufacturing process materials. In particular, the laminated film of the present invention can be suitably used as an electronics device circuit material in which an electric circuit such as a stretchable sensor is laminated by imparting adhesion to the printed layer, or as a substrate for a wearable / wearless sensor or a medical film substrate by applying a material with high water vapor permeability such as a polyurethane resin.
[0080] The laminated film of the present invention can be preferably used for sensor applications in which an elastic conductive layer is laminated. As the demand for wearable devices with health care functions increases with the expansion of health consciousness, wearable devices feel like they are being worn, and resistance to wearing them for long periods of time is increasing. In the midst of this, the need for wearless devices that can be used without feeling like they are being worn is increasing, and sensor devices for measuring vital signs (brain waves, pulse, veins, etc.) that can be attached directly to the skin, etc., are attracting attention. Such sensor members are provided with elastic electronic board circuits, and due to the characteristic that the electrical resistance does not change even when deformed, those that can be used even when wrapped around the human body, etc. are being considered. In addition, by incorporating a touch sensor element on the surface of the laminated film of the present invention, it can be developed as a display material as a film-like device that can input characters, etc. As such sensors, electrostatic capacitance sensors that are inexpensive, lightweight, and can be made thin may be used, and resistance sensors, piezo sensors using piezoelectric polymers, energy harvesting sensors using triboelectric charging, etc. may be used. In particular, sensor materials laminated with such stretchable conductive layers can be used not only for the vital signs sensor applications mentioned above, but also for slimming down integrated circuits by bonding them to curved plastic materials, or as flexible film materials that contribute to making electronic component modules smaller and thinner.
[0081] Since the above-mentioned sensor is preferably used within the temperature range of body temperature or the display, it is particularly preferable that the shape or function can be changed for use within a temperature range of 20 to 100° C. Note that changing the function refers to changing the function obtained as a laminate film by changing the mechanical and optical properties by changing the overall or partial shape of the laminate film.
[0082] The sensor that can be used by changing its shape at the above temperature may be a sensor that softens in the above temperature range and is used continuously in the softened state by touching the temperature, or a type of sensor that changes its shape at a specific temperature (shape change point Tn) or higher, is installed so as to follow a predetermined shape, and then is solidified by lowering the temperature. For example, when a material having a stretchable conductive layer laminated thereon is used as a vital sensor, the device stretches in response to the movement of the body after being worn, but if it is a sensor for monitoring heart rate, pulse, body temperature, etc. like current wearable terminals, it can be used by following the shape by stretching up to about 20 to 30% on the arm or chest. On the other hand, an elongation rate of more than 50% may be required in the joint part. In that case, the film material of the present invention that shows elastic deformation even at an elongation rate of 50% or more and is less likely to retain distortion can be suitably used. Examples of applications requiring an elongation rate of 50% or more include sensor materials that measure the movement behavior of artificial joints and sensor materials equipped with acceleration sensors for monitoring daily movements. It is also suitable for use as a biosensor with a power storage function that utilizes a piezoelectric sensor that responds with high sensitivity to distortion and vibration caused by joint movements. Such a sensor may be a material in which a conductive layer is directly laminated onto a film, or a material consisting of a combination of a sensor portion that has been given conductivity and a base film that comes into direct contact with the skin.
[0083] As an example of a sensor whose function can be changed by changing the temperature, there is a sensor material whose light transmittance, diffusion, and light collection can be switched by changing the surface shape. In this case, it can be expressed by performing a surface treatment having a certain shape in the depth direction from the outermost surface of the laminated film over 10 to tens of layers. For example, by providing a rounded convex surface shape as a surface treatment, it can be used as a material that changes the angle of incidence of light from the outside and collects light, or by providing a pointed convex surface shape, it can be used as a material that diffuses light from the outside / inside. It is expected that the surface shape can be converted to a flat shape by softening it at a certain temperature or higher and deforming it by applying pressure from the outside to crush the shape, and that the material can be switched to a material with high parallel light transmittance. Furthermore, when a thermal stimulus of a certain temperature or higher is applied, it can be restored to the original surface-treated shape. In this way, by using the laminated film having a highly stimuli-responsive multilayer laminated structure of the present invention, it can be expected to be used as a sensor that can be used repeatedly as a light sensor material.
[0084] The laminated film of the present invention is preferably used as a tape with a urethane-based or silicone-based adhesive layer on at least one side of the laminated film as a substrate for use in a medical film or a film for sanitary materials, which is to be applied to the human body. Examples of adhesives include acrylic adhesives, urethane-based adhesives, silicone-based adhesives, and rubber-based adhesives. As a tape substrate for use in application to the human body, it is preferable to use urethane-based adhesives, which are less irritating to the skin and have excellent air escape properties and removability, and silicone-based adhesives, which are more adhesive and have less effect on dry skin, than acrylic adhesives, which have strong adhesive power and cause great damage to the skin when peeled off, and rubber adhesives, which are of concern for allergy. These adhesives may be directly laminated to the laminated film substrate, or, in order to improve adhesion, a primer layer that improves adhesion may be provided in advance on the surface of the laminated film, and an adhesive layer may be provided directly on the primer layer.
[0085] This type of tape can be used by sticking it to a flat surface with an adhesive like a normal bandage, but since it has the particular feature of being able to change and restore its shape even when applied to areas with high elasticity, it can be ideally used as a joint support tape, sports tape, or fixation tape for sprains and fractures, etc., as a tape that can be used repeatedly while changing its shape according to the progress of treatment, etc.
[0086] Such tapes have a water vapor transmission rate of 300(g·25μm / (m 2 ·day)) or higher, and the material should preferably be one that can be used by changing its shape and function in a temperature range of 20 to 50°C. Since it is preferable for the tape base material to be one that can be applied to the human body and used for long periods of time by changing its shape, it is required to have a water vapor transmission rate that does not interfere with skin breathing at the site where the tape is applied. In addition, the tape base material is preferably required to have a property that it can be fixed in shape to conform to the human body and can be easily removed, and it is preferable for the tape to exhibit shape fixation / recovery behavior in a temperature range of 50°C or less where human skin does not feel hot even when touched for long periods of time. In addition, the water vapor transmission rate should be 800(g·25μm / (m 2 It is preferable that the period is longer than 10 days.
[0087] Next, a preferred method for producing the laminated film of the present invention will be described below, although it is to be understood that the present invention is not limited to such an example.
[0088] The thermoplastic resins constituting each thermoplastic resin layer of the laminated film are prepared in the form of pellets or the like. The pellets are dried in hot air or under vacuum as necessary, and then fed to separate extruders. When additives are added to the thermoplastic resin, powder, granule, or liquid additives may be kneaded and dispersed in a desired ratio during the main extrusion process by a top feed or side feed method, or master pellets in which the additives have been dispersed in the thermoplastic resin in advance may be fed. In the extruder, the thermoplastic resin is heated and melted to a glass transition temperature or above in the case of an amorphous thermoplastic resin, or to a melting point or above in the case of a crystalline thermoplastic resin, and the extrusion amount of each thermoplastic resin is made uniform by a gear pump or the like, and foreign matter and modified resins are removed through a filter or the like. These thermoplastic resins are formed into a desired laminate through a lamination device, and then discharged from a die in the form of a sheet. The molten sheet discharged from the die is then extruded onto a cooling body such as a casting drum, where it is cooled and solidified to become a cast sheet. Casting At this time, it is preferable to use a wire-shaped, tape-shaped, needle-shaped, or knife-shaped electrode to bring the thermoplastic resin into close contact with a cooling body such as a casting drum by electrostatic force, and rapidly solidify the resin. Also preferred are methods in which air is blown from a slit-shaped, spot-shaped, or planar device to bring the sheet into contact with a cooling body such as a casting drum and then rapidly solidify the sheet, or methods in which the sheet is rapidly solidified by bringing the sheet into contact with a cooling body using a nip roll. As an auxiliary, a liquid with good wettability such as liquid surfactant water or liquid paraffin can be applied to the surface of the casting drum to provide adhesion. Furthermore, when it is difficult to bring the molten sheet into contact with the cast and then solidify the sheet by electrostatic force, another preferred method is to introduce the molten sheet into two rolls provided with a specific gap therebetween and then cool and solidify the sheet from both sides.
[0089] As described above, the laminated film of the present invention preferably uses a crystalline thermoplastic resin with a low glass transition temperature as the outermost layer, but the resin disposed on the outermost surface of the laminated film may exhibit tackiness and may easily adhere to the casting drum. Therefore, it is preferable to apply a release agent (fluorine-based, silicon-based, wax-based, etc.) to the surface of the casting drum, or to use a matte roll or a fluorine roll as the roll material.
[0090] As the multi-layer lamination device, a multi-manifold die, a feed block, a square mixer, etc. can be used, but in particular, in order to efficiently obtain the multi-layer laminate of the present invention, it is preferable to use a feed block having a fine slit. When such a feed block is used, the device does not become extremely large, so the amount of foreign matter generated due to thermal deterioration is small, and high-precision lamination is possible even when the number of layers is extremely large. In addition, the lamination accuracy in the width direction is also significantly improved compared to the conventional technology. Furthermore, this device has the advantages that the thickness of each layer can be adjusted by the shape (length, width) of the slit, making it easy to achieve any layer thickness, and that the effect of the resin flow during the lamination process makes it easy to orient particles in the direction of the laminated sheet surface.
[0091] When a laminated sheet is produced using a slit-type feedblock, the thickness and distribution of each layer can be adjusted by adjusting the pressure balance by changing the length and width of the slit. The length of the slit refers to the length of the comb teeth that form the flow path for alternately flowing layers A and B inside the slit plate. In addition, after forming a laminate in the feedblock, a method can be used in which the number of layers is doubled by stacking them through a square mixer to increase the number of layers.
[0092] The obtained cast sheet may be subjected to the following stretching step as required to remove distortion of the laminated sheet in advance to suppress deformation after use or to utilize the shrinkage behavior so that it can be used immediately. The stretching step may involve uniaxial stretching in a specific direction, either the longitudinal direction (the conveying direction in the manufacturing process of the laminated sheet) or the transverse direction, or biaxial stretching in the longitudinal direction and the transverse direction. When biaxial stretching is performed, it may be performed biaxially sequentially or simultaneously.
[0093] First, uniaxial stretching and sequential biaxial stretching in which the sheet is stretched in the longitudinal direction and then in the width direction will be described. Here, stretching in the longitudinal direction refers to uniaxial stretching for giving the sheet a molecular orientation in the longitudinal direction, and is usually performed by the difference in peripheral speed of the rolls. This stretching may be performed in one stage, or in multiple stages using a plurality of pairs of rolls. The stretching ratio varies depending on the type of resin, but in the present laminated film, the layer stretching ratio is preferably 1.1 to 3.0 times, and particularly preferably 1.1 to 2.0 times. If the ratio is increased, the influence of permanent deformation of the thermoplastic resin is likely to occur, and since the influence on the dimensional recovery rate is large, the stretching ratio is preferably within the above-mentioned preferred stretching ratio range. In addition, the stretching temperature is preferably set within the range of the glass transition temperature +10°C to the glass transition temperature +100°C of the resin constituting the sheet. The uniaxially stretched laminated sheet obtained in this manner can be subjected to surface treatment such as corona treatment, frame treatment, and plasma treatment as necessary, and then a primer layer can be formed to improve adhesion with the film to be laminated on the upper part. In the in-line coating process, the primer layer may be applied to one side or to both sides simultaneously or one side at a time.
[0094] The stretching in the width direction means stretching for giving the sheet a width direction orientation, and is usually performed by conveying the sheet while holding both ends with clips using a tenter. The stretching ratio varies depending on the type of resin, but is usually preferably 1.1 to 3.0 times, and particularly preferably 1.1 to 2.0 times. The stretching temperature is preferably the glass transition temperature + 10°C to the glass transition temperature + 100°C of the resin constituting the sheet and not more than the melting point Tm.
[0095] Next, the case of simultaneous biaxial stretching will be described. In the case of simultaneous biaxial stretching, the obtained cast sheet may be subjected to surface treatment such as corona treatment, frame treatment, plasma treatment, etc., as necessary, and then functions such as easy slip, easy adhesion, and antistatic properties may be imparted by in-line coating. In the in-line coating process, the coating layer may be applied to one side of the sheet, or may be applied to both sides simultaneously or one side at a time.
[0096] Next, the cast sheet is introduced into a simultaneous biaxial tenter, and conveyed while both ends of the sheet are held by clips, whereby the sheet can be stretched simultaneously and / or stepwise in the longitudinal and transverse directions. The simultaneous biaxial stretching machine (tenter) may be of the pantograph type, screw type, drive motor type, linear motor type, etc., but the drive motor type or linear motor type, which can change the stretching ratio at any desired position and can perform relaxation treatment at any desired position, is preferred. The stretching ratio varies depending on the type of resin, but is usually preferably 1.1 to 4.0 times as an areal ratio, and more preferably 1.1 to 2.0 times. The stretching speed may be the same or different speeds in the longitudinal and transverse directions. The stretching temperature is preferably the glass transition temperature of the resin constituting the alternating laminate unit +10°C to the glass transition temperature +100°C.
[0097] The laminated film obtained in the above manner is trimmed to a required width by a winding device and wound in a roll state so as to prevent wrinkles from forming during winding. In addition, embossing may be performed on both ends of the film to improve the roll shape during winding.
[0098] The thickness of the laminated film of the present invention is not particularly limited, but considering the trend toward thinner functional films, stable cast film-forming speed, and the expected applications of base films for medical, industrial, and consumer use, it is preferably 20 μm or more and 1 mm or less. Considering roll winding properties, it is more preferably 500 μm or less. Although there is no lower limit, in order to ensure stable roll winding properties even under high-speed casting conditions and to form a film without tearing, it is practically preferable for the thickness to be 20 μm or more.
[0099] The thickness of the laminated film is not particularly limited, but it is preferable to adjust the thickness by increasing or decreasing the lip gap of the die, the take-up speed of a cooling body such as a casting drum, etc. In order to suppress the film width shrinkage caused by an increase in the take-up speed, it is preferable to appropriately adjust the gap between the die and the cooling body. When the film width cannot be kept constant, for example, the stretch ratio in the width direction can be made constant by adjusting the distance between the clips in the tenter.
[0100] In addition, a functional layer for adding functions such as scratch resistance and abrasion resistance may be laminated on the outermost surface of the laminate film of the present invention. When the laminate film is transported roll-to-roll in the film-forming transport process or processing process, the occurrence of scratches on the laminate film surface due to friction between the roll and the film can be prevented. In addition, in consideration of improving weather resistance and suitability for use, an ultraviolet absorbing layer, an adhesive layer, a gas barrier layer containing metal oxides, etc., a release (anti-tackiness) layer, a printing layer, a conductive layer, etc. may be formed. These layers may be one layer or multiple layers, and one layer may have multiple functions. EXAMPLES
[0101] The present invention will be described below with reference to examples, but the present invention is not limited to these examples. Each characteristic was measured by the following methods.
[0102] (Methods for measuring characteristics and evaluating effects) The methods for measuring the characteristics and evaluating the effects of the present invention are as follows.
[0103] (1) Differential scanning calorimetry (DSC) A differential scanning calorimeter EXSTAR DSC6220 manufactured by Hitachi High-Technologies Corporation was used. Measurements and temperature readings were performed in accordance with JIS-K-7122 (1987). Specifically, when approximately 5 mg of a sample was placed on an aluminum tray and heated at a rate of 20°C / min in the temperature range from -80°C to 280°C, the glass transition temperature (°C) was determined as the temperature corresponding to the inflection point of the step transition, and the melting point Tm (°C) corresponding to the endothermic peak was determined. In addition, the measurement of each layer was performed in the same manner by peeling and extracting only the portion of each layer.
[0104] (2) Acquire a cross-sectional image of the laminate (when the layer thickness is 5 μm or more) The layer structure information of the laminated film was obtained by observing the samples sliced using an ultramicrotome with a digital microscope according to the thickness of each layer. Specifically, a Keyence VHX-5000 digital microscope was used, equipped with a lens that allows observation at a maximum magnification of 1000x, to obtain cross-sectional images to analyze the layer structure (number of layers, regular arrangement, layer thickness distribution) and the thickness of each layer.
[0105] (3) Acquiring a cross-sectional image of the laminate (when the layer thickness is less than 5 μm) The layer structure information of the laminated film was obtained by observing the sample sliced using an ultramicrotome with a transmission electron microscope (TEM) according to the thickness of each layer. Specifically, a transmission electron microscope JEM-1400 Plus (manufactured by JEOL Ltd.) was used to observe the cross section of the laminated film (thickness direction, i.e., cross section perpendicular to the film surface) at an acceleration voltage of 100 kV, and the layer structure (number of layers, regular arrangement, layer thickness distribution) and each layer thickness were analyzed by obtaining a cross-sectional image. In addition, a staining technique using an electronic staining agent (RuO4, etc.) was used to obtain a large contrast difference between each layer. In addition, according to the thickness of each layer, observation was performed at a direct magnification of 40,000 times when the thin film layer thickness was less than 100 nm, at a direct magnification of 20,000 times when the thin film layer thickness was 100 nm or more and less than 500 nm, and at a direct magnification of 1,000 to 10,000 times when the thin film layer thickness was 500 nm or more.
[0106] (4) Layer thickness analysis The cross-sectional image obtained in this transmission electron microscope observation was converted into a compressed image file (JPEG), and position-brightness data was obtained by line profile along the thickness direction of the laminated film using ImagePro-10 manufactured by MediaCybernetics. Then, a five-point moving average process was performed on the profile obtained by plotting the relationship between position and brightness using a spreadsheet software (Microsoft Corporation "Excel" (registered trademark) 2016). The average process was performed by performing an average process of brightness for five consecutive measurement positions, changing the position one point at a time and continuously processing the same calculation, and an averaged position-brightness profile was obtained. In the obtained averaged position-brightness profile, the position surrounded by the inflection points where the slope changes from positive to negative or negative to positive was determined to be one layer. For each layer obtained by this method, position-brightness data was then obtained in the planar direction (direction perpendicular to the thickness direction) of the laminated film. After calculating the average value and standard deviation of the brightness obtained for each layer, if the difference between the average values of the brightness of the two adjacent layers was greater than any of the standard deviations of the brightness of the adjacent thermoplastic resin layers, these two adjacent layers were determined to be different. At this time, the difference (distance) in the positions between the inflection points was calculated as the layer thickness of each layer.
[0107] (5)Lamination ratio The lamination ratio of the laminate film was calculated using the layer thickness of each layer calculated by the methods described in (2) to (4). Specifically, the total value of the layer thicknesses of each layer exhibiting the same contrast contained in the laminate film was calculated, and the total value of the layer thickness of layer A relative to the total layer thickness of layer B contained in the laminate film was calculated as the lamination ratio.
[0108] (6) AFM tapping measurement (measuring elastic modulus and tan δ of each layer) The cross-section of the sample cut using an ultramicrotome was evaluated using a Bruker scanning probe microscope NanoScopeV. The laminated film was heated to the desired temperature in a thermostatic chamber, and the silicon cantilever NCHR was used as a probe. The cantilever was moved vertically continuously in the thickness direction of the laminated film in peak force tapping mode, and measurements were taken at a sweep speed of 0.3 to 0.5 Hz / s to obtain continuous change data on the elastic modulus (storage modulus, loss modulus). The storage modulus or loss modulus of each layer was determined by judging the distribution of the "different" thermoplastic resin layers and the entire laminated film, and then the elastic modulus data of five layers of the same thermoplastic resin layers were measured and averaged. The tan δ of each layer at a specific temperature was calculated by dividing the loss modulus measured at that temperature by the storage modulus.
[0109] (7) Loss tangent (tan δ) analysis by dynamic viscoelasticity measurement Based on the tensile vibration non-resonance method of JIS K7244-4 (1999) (this is called the dynamic viscoelasticity method), a loss tangent spectrum was obtained using a dynamic viscoelasticity measuring device DMS6100 manufactured by Seiko Instruments Inc. The detailed measurement conditions were as follows: Measurement mode: "Tension", chuck distance: "20 mm", specimen width: "10 mm", frequency: "10 Hz", strain amplitude: "10 μm", minimum tension: "20 mN", initial force amplitude: "40 mN", measurement temperature: "-80°C to Tm°C", heating rate: "2°C / min".
[0110] (8) Electron energy loss spectroscopy (EELS) A cut sample of the cross section (thickness direction cross section) of the measurement target was prepared by ultra-thin sectioning using an ultramicrotome. The dielectric constant of the cut sample was measured using an atomic resolution analytical electron microscope ARM200F manufactured by JEOL. Specifically, after acquiring a HAADF-STEM (High Angle Annular Dark-Field Scanning Transmission Electron Microscopy) image at an acceleration voltage of 80 kV and a beam spot size of 0.2 mmφ, a multi-point analysis (60 × 60 pixels, 20 nm / pixel) was performed on the layer to be measured in 50 msec to obtain data on energy loss and electron beam intensity. The same operation was performed on three points for the same thermoplastic resin layer in the laminated film to obtain spectrum data with improved S / N ratio. From the obtained spectrum data, background correction due to elastic scattering and removal of multiple scattering effects were performed, and the dielectric function of each layer was calculated by the Kramers-Kronig transformation shown in formula (4). The integral range during Kramers-Kronig transformation was set to 0 to 200 eV. Based on the dielectric function of equation (4), the real and imaginary parts of the dielectric constant were calculated from equations (5) and (6), respectively, and then the dielectric constant was calculated from the square root of the sum of the squares of these, as shown in equation (7). Using the above method, the dielectric constant at a loss energy of 2.5 eV of each thermoplastic resin layer was calculated.
[0111] In formulas (4) to (7), Re is the real part, Im is the imaginary part, ε is the dielectric constant (average value), ε(ω) is the dielectric function, ε1 is the real part of the dielectric constant, ε2 is the imaginary part of the dielectric constant, and ω and ω' are angular frequencies.
[0112]
number
[0113]
number
[0114]
number
[0115]
number
[0116] (9) Permanent set measurement ("50% stretch molding - reheat cycle test") The laminated film was cut into strips with a width of 1 cm and a length of 15 cm, and a mark was placed in the center 10 cm. The exact distance between the marks (d [mm]) was measured using a Nikon V-16A projector. Five samples with the measured length were stretched in the longitudinal direction at 1.5 times (50% strain) using a Bruckner stretcher KARO-V in a stretch zone set to Tn+20°C for the laminated film after preheating for 60 seconds. The stretched sample was returned to the insert position, held by the clip for 30 seconds, and then the clip was released to obtain a stretched sample. The obtained sample was then heat-treated for 1 minute under no load in a hot air oven at Tn+20°C, and the distance between the marks of the obtained sample was measured. The average value of the calculated values for each of the five samples was adopted as the sample length after the first cycle test. The cycle of 1.5 times stretching, cooling and solidifying, and reheating is referred to as the "50% stretch molding-reheating cycle test."
[0117] This cycle test was repeated five times for the same sample, and the sample length was measured after each cycle test. The initial sample length and the sample lengths after the first to fifth cycle tests were plotted on a spreadsheet software (Microsoft Corporation "Excel" (registered trademark) 2016) with the number of times on the horizontal axis and the sample length on the vertical axis to calculate an exponential approximation curve. The sample length d∞ when n = ∞ was calculated, and the permanent set was estimated according to formula (2).
[0118]
number
[0119] (10) Young's modulus measurement of laminated film Measurements were made using a "Tensilon" (registered trademark) universal testing machine RTG1210 (manufactured by Orientec). Strip-shaped samples 150 mm long x 10 mm wide were cut out in the machine direction (MD) and transverse direction (TD) of the film, and tensile tests were performed under the following conditions. Young's modulus was calculated from the obtained load-strain curve. The measurement was performed five times for each sample, and the average value was used as the measured value. Measurement temperature / humidity: 23℃, 65%RH Initial tension chuck distance: 50mm Tensile speed: 300 mm / min (11) Shape fixation / restoration functionality evaluation of laminated film The "50% stretch molding-reheat cycle test" was repeated five times for the same sample, and the distance between the marks (sample length) before the first test was d, the distance between the marks (sample length) before the start of the fifth cycle test was d4, the distance between the marks after the fifth 50% stretch cooling was d4', and the distance between the marks after the fifth cycle test was d5. The dimensional fixation rate and dimensional recovery rate after the five cycle tests were calculated according to formulas (8) and (9). The average values calculated for each of the five samples were adopted as the dimensional fixation rate and dimensional recovery rate values in the fifth cycle test. Based on these values, the superiority or inferiority of the shape fixation / recovery ability was judged according to the following evaluation.
[0120]
number
[0121]
number
[0122] S: After five repeated tests, the shape retention is high at approximately 100%, and the shape recovery is also high at over 95%. A: After five repeated tests, the shape retention was high at about 100%, but the recovery rate was slightly lower at 90% to less than 95%. B: After five repeated tests, the shape retention is 95% or more, and the recovery is slightly inferior at 80% to less than 90%. C: After five repeated tests, the shape retention was 90% or more but less than 95%, and the recovery was also slightly inferior at 80% or more but less than 95%. N: Does not meet the criteria C above or does not exhibit shape restoration properties (12) Stiffness of laminated film The laminated film was cut into a strip of 1 cm width and 15 cm length, and the sample was softened by heating for 1 minute in a hot air oven set at Tn+20℃, and then quickly wrapped in a spiral shape around a metal rod with a diameter of 2 cm so that the long sides of the strip of film were in contact with each other, and then air-cooled for 3 minutes to obtain a spiral molded product. After counting the number of spiral turns of this molded product, one end was fixed and the other end was hung at room temperature with a 15g load between them, and the number of spiral turns of the laminated film was counted after leaving it to stand for 1 day, and the rigidity of the laminated film was determined as follows: A: The number of spiral turns did not change at all, and the rigidity of the laminated film was sufficiently high. B: The number of spiral turns decreased by less than 5% when a load was applied, but the rigidity of the laminated film was judged to be high. N: The number of spiral turns was smaller than that of the B grade above, and the rigidity was poor.
[0123] <Thermoplastic resin> Resin 1: Polytetramethylene ether glycol copolymerized polyethylene terephthalate resin with a glass transition temperature of -60°C and a melting point of 160°C Resin 2: Thermoplastic polyurethane resin with a glass transition temperature of -50°C and a melting point of 155°C Resin 3: Polyether block amide resin with a glass transition temperature of -65°C and a melting point of 144°C Resin 4: Polyethylene terephthalate resin copolymerized with 33 mol% cyclohexanedimethanol, exhibiting a glass transition temperature of 70°C Resin 5: Polyethylene terephthalate resin copolymerized with 20 mol% adipic acid and 10 mol% isophthalic acid, which has a glass transition temperature of 40°C. Resin 6: Polycaprolactone resin with a glass transition temperature of -65°C and a melting point of 60°C Resin 7: Polyvinyl alcohol resin with a glass transition temperature of 40°C and a melting point of 164°C Example 1 Resin 1 and resin 4 were used as the thermoplastic resins constituting the thermoplastic resin layers A and B, respectively. Each of the prepared thermoplastic resins was fed in pellet form into two separate twin-screw extruders, melted at 260°C and 270°C, respectively, and kneaded. The kneading conditions were set so that the screw rotation speed relative to the discharge amount was 0.7 in all cases. Next, after passing through seven FSS-type leaf disc filters, the mixture was joined in a feed block with nine slits, whose temperature was adjusted to 270°C, while being metered with a gear pump, to form a nine-layer laminate with a lamination ratio of 1.0, laminated in a regular arrangement of (AB)n in the thickness direction, and both surface layers being A layers. The feed block with nine slits used here was designed so that the thickness of both surface layers was 10 times that of the remaining layers. The molten laminate that passed through the feed block was then fed to a T-die and molded into a sheet, after which it was quenched and solidified on a casting drum coated with a silicone-based release agent while applying an electrostatic voltage of 8 kV with a wire, with the surface temperature kept at 10°C, to obtain an unstretched laminate sheet. The casting drum speed was then increased and adjusted so that the laminate film thickness was 250 μm, obtaining the desired laminate film. The evaluation results of the obtained laminate film are shown in the table.
[0124] Comparative Example 1 A laminate film was obtained in the same manner as in Example 1, except that a resin obtained by mixing Resin 1 and Resin 4 in a mass ratio of 50:50 was used as the thermoplastic resins constituting the thermoplastic resin layers A and B, and the extrusion temperature was 270° C. The evaluation results of the obtained laminate film are shown in the table.
[0125] (Comparative Examples 2 and 3) A laminate film was obtained in the same manner as in Comparative Example 1, except that a resin obtained by mixing Resin 1 and Resin 4 in the mass ratio shown in the table was used as the thermoplastic resin constituting each of the thermoplastic resin layers A and B. The evaluation results of the obtained laminate film are shown in the table.
[0126] (Examples 2 to 10, Comparative Examples 4 and 5) A laminate film and a molded product were obtained in the same manner as in Example 1, except that the number of layers in the feed block and the extruder output (thickness ratio within the regular arrangement) were changed as shown in the table. The feed blocks with different numbers of layers were all designed so that the surface layer was 10 times thicker than the other layers. The evaluation results of the obtained laminate film are shown in the table.
[0127] Example 11 In comparison with Example 2, three square mixers capable of doubling the number of layers by dividing the molten laminate in the center and overlapping them were combined directly below the 51-layer feed block. Theoretically, the 51-layer molten laminate forms a laminate with a layering ratio of 1.0 having 401 layers after being extruded from the die, but the laminate film actually obtained had some disorder in the lamination of both resins, and only 381 layers could be counted. The evaluation results of the obtained laminate film are shown in the table, but due to the disorder in the lamination, the performance was inferior to that of Example 10.
[0128] (Examples 12 to 15) A laminate film was obtained in the same manner as in Example 7, except that the resins used as thermoplastic resins A and B in Example 7 were changed as shown in the table. The evaluation results of the obtained laminate film are shown in the table.
[0129] [Table 1]
[0130] [Table 2]
[0131] [Table 3]
[0132] [Table 4] [Industrial Applicability]
[0133] In the present invention, a multi-layer laminate structure is used as the basic structure, and a material having a structure in which a polymer with high elasticity and a polymer with high rigidity are alternately laminated can exhibit a high degree of shape fixation and shape recovery when deformed in a specific direction, regardless of the combination, compatibility, or ratio of the polymers. This makes it possible to use the material as a flexible and strong film substrate that can be used while repeatedly deforming and recovering over a long period of time. The material can be suitably used as a sensor substrate, medical film, or film for sanitary materials, which require particularly high flexibility and stretchability. [Explanation of symbols]
[0134] 1: Spectrum showing the relationship between the depth and contrast (gray level) change in the thickness direction of a laminated film with (AB)n regular arrangement 2: Layer thickness of layer A 3: Layer thickness of layer B 4: Loss tangent tanδ spectrum obtained by dynamic viscoelasticity measurement 5: Temperature T1 6: Loss tangent peak occurring at the lowest temperature 7: Temperature T2 8: Loss tangent peak that occurs at the highest temperature in the temperature range below the melting point Tm 9: tan δ1 10: tan δ2 11: Loss tangent peak occurring at temperatures different from T1 and T2 12: Differential calorimetry spectrum 13: Glass transition temperature that appears in the lowest temperature region 14: Glass transition temperature appears in the region below the melting point Tm 15: Melting point Tm derived from crystalline thermoplastic elastomer 16: Temperature range between the glass transition temperature and the melting point (Tm) of this resin 17: Glass transition temperature 18: Exponential approximation curve derived from dimensional change rate results 19: Permanent Deformation 20: Strain-stress curve in tensile test 21: Inflection point (upper yield point) when differential analysis is performed 22: Magnitude of permanent deformation
Claims
1. A laminated film having a structure in which nine or more layers of A layers made of a thermoplastic resin A and B layers made of a thermoplastic resin B different from the thermoplastic resin A are alternately laminated, wherein when dynamic viscoelasticity measurement is performed at a frequency of 10 Hz over a temperature range from -80°C to Tm described below, the laminated film has two or more loss tangent (tan δ) peaks, and the relationship between the tan δ peak tan δ1 occurring at the lowest temperature (temperature T1 (°C)) and the tan δ peak tan δ2 occurring at the highest temperature (temperature T2 (°C)) is tan δ2 / tan δ1≧1.
0. In accordance with JIS K-7122 (1987), the highest melting point of the laminate film obtained by differential scanning calorimetry using a 5 mg sample at a heating rate of 20°C / min is defined as Tm, the highest glass transition temperature or melting point appearing in the region lower than Tm is defined as Tn, and the layer whose melting point is within ±5°C of the highest melting point Tm of the laminate film is defined as layer A, and the layer whose glass transition temperature or melting point, whichever is higher, is within ±5°C of Tn of the laminate film is defined as layer B.
2. The laminate film according to claim 1, wherein, when the loss tangent of layer A at temperature T (°C) is tan δA(T) and the loss tangent of layer B is tan δB(T), tan δA(T1)>tan δB(T1) and tan δA(T2)<tan δB(T2).
3. 3. The laminated film according to claim 1, which has a permanent deformation of 15% or less when a 50% strain is applied at Tn+20°C.
4. The laminated film according to claim 1 or 2, wherein the thermoplastic resin A is crystalline.
5. 3. The laminated film according to claim 1, wherein the thermoplastic resin B is amorphous and the glass transition temperature of the B layer is Tn.
6. 3. The laminated film according to claim 1, wherein in the strain-stress curve in the tensile test at Tn+20° C., an inflection point appears for the first time at a strain of 50% or more when differential analysis is performed.
7. 3. The laminated film according to claim 1 or 2, wherein, when the storage modulus of layer A at temperature T (° C.) is GA(T) (GPa) and the storage modulus of layer B is GB(T) (GPa), 1.2GA(Tn-10)<GB(Tn-10) and GA(Tn+10)≧1.2GB(Tn+10) are satisfied.
8. 3. The laminated film according to claim 1, wherein the lamination ratio is 0.3 or more and 1.5 or less.
9. 3. The laminated film according to claim 1, wherein the main component of the thermoplastic resin A is any one of polystyrene, polyester, polyurethane, and polyamide.
10. A sensor comprising the laminate film according to claim 1 or 2 and a stretchable conductive layer laminated thereon.
11. The sensor according to claim 10, which is used with its shape and function changed in a temperature range of 20 to 100°C.
12. 3. A tape comprising the laminate film according to claim 1 or 2 and an acrylic or silicone adhesive layer provided on at least one surface of the laminate film.
13. The tape according to claim 12, which is used while changing its shape and function in a temperature range of 20 to 50°C.
Citation Information
Patent Citations
Polyester molding having capability of shape memory
JP1992122712A
Shape-memory vulcanized rubber molding
JP1997309986A
Stretchable film
JP2017133011A
Thermoplastic shape memory resin sheet and article including thermoplastic shape memory resin sheet
JP2021023499A